Trump's Democrats - Muravchik, Stephanie, 1970-; Shields, Jon A. (Washington, D.C. Brookings Institution Press, 2020)
"Will they do so again in 2020? Looking for answers, Muravchik and Shields lived in three such "flipped" blue communities, finding that these voters still like the Democratic Party, but it's not the party many of this book's readers will recognize. In these communities, some of the most beloved and longest-serving Democratic leaders are themselves Trumpian-grandiose, combative, thin-skinned, nepotistic. Indifferent to ideology, they promise to take care of "their people" by cutting deals-and corners if needed. Stressing loyalty, they often turn to family to fill critical political roles. Trump strikes a familiar figure to these communities, resembling an old-style Democratic boss. Although Trump's Democrats have often been pictured as racists, Muravchik and Shields find that their primary political allegiances are to their town or county-not racial identity. They will spend an extra dollar to patronize local businesses, and they think local jobs should go to their neighbors, not "foreigners" from neighboring counties-who are just as likely to be white and native-born. When these citizens turn their attention to the nation and their place in it, their thinking is informed by their sense of belonging in their town. Thus, America first reflects a way of imagining political community that resonates by analogy to the social and political life in the places they live. The good news for Democrats is that the appeal of Trump does not yet extend to the rest of the GOP. The Democratic Party can reclaim its historic place as the home of working and lower-middle-class Americans. The first step is to gain a better understanding of Trump's Democrats"--
Front Cover -- Front Flap -- Title Page -- Copyright Information -- Table of Contents -- Acknowledgments -- Introduction -- Three Democratic Communities -- Dragon Energy -- The Don -- America First -- Make America Great Again -- Democrats No More? -- Appendix: Long-Standing Democratic Counties that Voted for Trump -- Notes -- Index -- Back Flap -- Back Cover
Includes bibliographical references and index.
108352
Keywords: Trump, Donald, -- 1946-; Democratic Party (U.S.); Working class -- Political activity -- Voter support - Change -- Presidential election - 2016 -- United States